2003
DOI: 10.1590/s0100-84042003000200011
|View full text |Cite
|
Sign up to set email alerts
|

Efeito alelopático do extrato alcoólico do cravo-da-índia e eugenol

Abstract: -(Allellopathic effects of the alcoholic extract of clove and eugenol). Eugenol is a volatile phenolic compound, being the major constituent of clove oil. In this study it was observed that clove ethanolic extract and pure eugenol had an allelopathic effect on the germination of several seeds, as well as that some of these seedlings sprayed with the clove extract showed a lower dry mass accumulation. It was not observed long distance inhibition of seed germination due to volatilization of eugenol.Key words -Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
31

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 23 publications
0
13
0
31
Order By: Relevance
“…Entretanto, existe preocupação de que resíduos anestésicos possivelmente deixados na carne possam alterar as características organolépticas -aroma e sabor -naturais do peixe, a ponto de resultar na rejeição do produto pelos consumidores (Olsen et al, 2006;Ribas et al, 2007 (Mazzafera, 2003). Estudos têm demonstrado a eficiência do óleo de cravo e do eugenol em anestesiar peixes de clima tropical, como o tambaqui (Roubach et al, 2005) e o matrinxã (Vidal et al, 2008), e de clima temperado, como a truta (Velísek et al, 2005) e o salmão (Iversen et al, 2003).…”
Section: Introductionunclassified
“…Entretanto, existe preocupação de que resíduos anestésicos possivelmente deixados na carne possam alterar as características organolépticas -aroma e sabor -naturais do peixe, a ponto de resultar na rejeição do produto pelos consumidores (Olsen et al, 2006;Ribas et al, 2007 (Mazzafera, 2003). Estudos têm demonstrado a eficiência do óleo de cravo e do eugenol em anestesiar peixes de clima tropical, como o tambaqui (Roubach et al, 2005) e o matrinxã (Vidal et al, 2008), e de clima temperado, como a truta (Velísek et al, 2005) e o salmão (Iversen et al, 2003).…”
Section: Introductionunclassified
“…Comportamento semelhante foi observado por Medeiros e Lucchesi (1993) que usando extrato aquoso de ervilhaca (Vicia sativa L.) verificaram redução no comprimento de raízes de alface sem no entanto aumentar a matéria seca das plântulas. Da mesma forma, Mazzafera (2003) trabalhando com extrato alcoólico de cravo-da-Índia (Syzygium aramaticum) não verificaram redução na matéria seca de parte aérea de plântulas de tomate e trigo, apesar do potencial germinativo ter sido grandemente afetado. No entanto, outros autores observaram redução da massa seca como Oliveira et al (2011) O presente trabalho corrobora a importância da pesquisa de plantas medicinais para se investigar seus efeitos alelopáticos e abrir perspectivas para a produção de substâncias naturais no controle de plantas daninhas.…”
Section: Resultsunclassified
“…However, it can be observed that the less vigorous seeds (Campos Gerais) responded better to the essential oil components, considering that there were higher percentages compared to the control treatment. Nevertheless, Mazzafera (2003) reported that the effect on the seeds could be less vigorous.…”
Section: Germination and Vigor Of Seeds Treated With Essential Oilmentioning
confidence: 99%